Ministry of the Interior Decree No. 950 of the Year 2023 Amending Certain Provisions of Ministerial Decree No. 8180 of the Year 1996 Regulating the Foreigners’ Residence Inside the Arab Republic of Egypt = وزارة الداخلية قرار رقم 950 لسنة 2023 بتعديل بعض أحكام القرار الوزراى رقم 8180 لسنة 1996 بتنظيم إقامة الأجانب بأراضى جمهورية مصر العربية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic